Assessing the clinical, humanistic, and economic impact of early cancer diagnosis: a systematic literature review - Aguiar-Ibáñez, Raquel; Mbous, Yves Paul Vincent; Sharma, Sugandh; Chawla, Evanka (Frontiers in Oncology, 2025)
IntroductionThere is a clear consensus among healthcare providers on the advantages of early cancer detection and treatment. However, no in-depth review has yet fully presented the clinical, humanistic, and economic benefits of early cancer diagnosis compared to late detection across a broad range of tumor types.MethodsA systematic literature review was conducted to determine the clinical, humanistic, and economic benefits of early cancer diagnosis, as opposed to late diagnosis, as reported in non-interventional studies conducted worldwide. Searches were conducted using electronic databases (MEDLINE and Embase), conference repositories and grey literature. Observational studies in adults diagnosed with bladder cancer, gastric cancer, head and neck cancer (HNC), melanoma, non-small cell lung cancer (NSCLC), renal-cell carcinoma (RCC), and triple negative breast cancer (TNBC) were eligible for inclusion if they reported survival, health-related quality of life (HRQoL), healthcare resource utilization and/or costs, according to stage at diagnosis. Identified records were screened and extracted by two independent reviewers, and discrepancies were resolved by a third reviewer. The quality of studies was assessed using the Newcastle-Ottawa scale and the Larg and Moss adapted checklist.ResultsOf the 3,159 records identified, 103 studies were included in this review. The general trend showed worse clinical, humanistic, and economic outcomes when patients were diagnosed at a later stage compared to an earlier stage. Patients diagnosed at an earlier stage, had on average, substantially higher survival rates and lower mortality rates across all cancer types and incurred lower resource utilization and costs (with available evidence for patients with NSCLC, TNBC, and HNC), compared to those diagnosed at a more advanced/later stage. Limited evidence on the humanistic burden suggested that with a more advanced stage at diagnosis, patients with bladder cancer experienced reduced HRQoL.ConclusionEarly cancer diagnosis (i.e., cancer diagnosed at earlier stages or with lower grades) was associated with longer survival, improved quality of life and lower healthcare costs and resource utilization compared to diagnosis of cancer at later stages or higher grades, as reported by overall survival (OS) and HRQoL outcomes. These findings emphasize the importance of screening and early detection of cancer to improve outcomes among patients diagnosed with cancer.